Nurses activities managing the nosocomial infections in surgical profile departments - Gauryliūtė, Laura; Galdikienė, Nijolė (Slauga. Mokslas ir praktika, 2020)
Nosocomial infections (NI) are one of the biggest health problems associated with health care worldwide. According to the Institute of Hygiene, NI is the most common adverse event (30.7%) in personal health care institutions. Nowadays, the question is often raised whether it is possible to prevent nosocomial infections? It is not possible to completely prevent nosocomial infections, but they can only be reduced because there are always people with infections in the treatment facility, and the microorganisms easily spread through the hands, air and surfaces.According to the research data, the majority of nurses’ report having sufficient knowledge of nosocomial infections and almost all nurses involved in the research are able to assess the importance of risk factors.
Keywords: nosocomial infection; infection management; nursing activities; surgical profile section